The interaction between diversity of herbaceous species and history of planting, Masal's plantations, Guilan Province, Iran - HASSAN POURBABAEI; MASOUMEH ESKANDARI; MEHRDAD GHODSKHAH DARYAEI; MEHDI HEYDARI (Society for Indonesian Biodiversity, 2015)
Pourbabaei H, Eskandari M, Daryaei MG, Heydari M. 2015. The interaction between diversity of herbaceous species and history of planting, Masal's forests, Guilan Province, Iran. Biodiversitas 16: 84-88. The purpose of this study was to determine the relationship between the plantation age and diversity of herbaceous species. The study area is located in the Masal's plantations of Guilan in north of Iran. For this purpose, 60 plots were sampled by a randomized-systematic method throughout the study area in order to record the herbaceous species, the Whitaker's nested plot was applied and the minimal area was obtained 64 m2 (8 x 8 m). In order to evaluate the plant diversity, some indices including Shannon-Wiener's diversity (H'), species richness (S) and Smith-Wilson's evenness (Evar) were utilized. Results indicated that 31 herbaceous species were found in two plantations. There were significant differences between two sites regarding H' and Evar. Whereas, there was no significant difference in view of species richness between two sites. In addition, results revealed that older plantation has not caused to increase richness and evenness of species.